Traffic optimization model and improving mobility in urban environment Universidad Católica of Santa María - Arequipa 2015 - Juan Carlos Tejada Calderón (2017)
After analyzing and evaluating the impact area, different types of negative impacts caused by different internal and external agents were identified, being the highest traffic impact on the environment Campus San José de la UCSM. A methodological guide for traffic studies locally adapted version of the Methodological Guide for the Study of Regional Transport Systems of the Mexican Institute of Transportation, and the model for improving urban mobility and traffic optimization was used within the impact area campus San José de la UCSM, which will allow a more fluid traffic, increased road safety, fewer accidents, sustainable mobility and reducing pollution for the benefit of the university community and local residents.